ANALISIS PERBANDINGAN KINERJA BANK SYARIAH DAN BANK KONVENSIONAL - puspa dania puspa (Al Birru: Jurnal Keuangan dan Perbankan Syariah, 2023)
The key to the company's success is the company's ability to generate profits. In this study the data used are financial statements, in the financial statements there is also a profit component. To measure the company's ability to achieve profit is called profitability.This research was conducted to determine the advantages of PT.Bank Panin Dubai Tbk.&PT. Bank Rakyat Indonesiab (PERSERO) Tbk. and compare the performance of the two banks 2018-2021 for 4 periods using Profitability Analysis with the ratio of Gross profit margin, Net profit margin, Return on assets, Return on equity.This research and discussion concludes that for 4 years from the 2018-2021 period the financial performance of Panin Dubai Syariah Bank and BRI Bank is based on the results of the calculation of the profitability ratios of gross profit margins, net profit margins and assets. research on Islamic banks, namely Bank Panin Dubai Syariah and conventional banks, namely Bank BRI, it can be concluded that their income from 2018 to 2021 is in good condition and maximum income.